Analisa Aktivitas Antibakteri Rebusan Daun Sirih Dengan Rebusan Daun Kemangi Terhadap Pertumbuhan Bakteri Streptococcus mutans - ENNY WILLIANTI; THEODORA; WAHYUNI DYAH PARMASARI (HANG TUAH MEDICAL JOURNAL, 2020)
ABSTRACT Background: Betel leaf contains essential oils consisting of bethelphenol, kavikol, sesquiterpenes, hydroxycavikol, cavibetol, estragol, eugenol and carvacrol. Essential oils are antibacterial due to the presence of phenol compounds and their derivatives that can denature the bacterial cell proteins. Basil leaves contain compounds from essential oils, namely 1,8-cineole, ß-bisabolene, and methyl eugenol. These three ingredients are soluble to ethanol and can cause damage to the cell membranes of the Streptococcus mutans bacteria, which are members of the normal oral flora but can turn into pathogens if the balance of normal flora is disturbed. The aim of this study was to determine the difference in the activity of the antibacterial of decoction betel leaf (piper betle L. ) with a decoction of basil leaves (ocimum sanctum) against growth of bacteria Streptococcus mutans (in vitro study). Method: this observational research with disk diffusion techniques. This study observed and measured the diameter of the inhibitory zone in MHA formed by decoction of betel leaf (piper betle L) and basil leaf (ocimum sanctum) in units of millimeters (mm). There were 2 groups with 16 replications. Results: the results of the description test showed that the antibacterial activity of the betel leaf decoction and the highest decoction of basil leaf was 17 mm and the lowest was 15 mm, but the average antibacterial value of betel leaf decoction (15,81) greater than the average value of antibacterial activity of basil leaf (15.75). This is because there are chemicals contained in betel leaf similar as contained in basil leaf, namely essential oils. Conclusion: there is no difference in the antibacterial activity of decoction betel leaf with decoction basil leaf against growth of bacteria Streptococcus mutans.